The Role of Textbooks to Support Scientific Approach Learning Implementation on Vocational High School (Book Review of Mechanics and Machine Elements for SMK Class X) - Riana Nurmalasari; Eddy Sutadji; Blima Oktaviastuti; Sunardi Sunardi (JPP (Jurnal Pendidikan dan Pembelajaran))
Abstract: Textbooks are one of the supporting learning processes and must be prepared according to the applicable curriculum, namely the 2013 curriculum. In fact, not all books used in the learning process currently have quality content and relevant content suitability. Moreover, not all textbooks have been prepared using a scientific approach. One of the textbooks that need to be reviewed is the Mechanics and Machine Elements for Class X on Vocational High Schools. There is a need for a study related to the suitability of the contents of the books according to KI and KD and adjust to aspects of the appropriateness of content, language, presentation, and graphics of textbooks. The preparation of the book must also be adjusted to the scientific approach in accordance with the 2013’s curriculum.